Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10620-015-3859-6
|View full text |Cite
|
Sign up to set email alerts
|

Population, Epidemiological, and Functional Genetics of Gastric Cancer Candidate Genes in Peruvians with Predominant Amerindian Ancestry

Abstract: Our updated meta-analysis reinforces the role of PTGS2-rs689466-A in gastric cancer in Asians, although more studies that control for ancestry are necessary to clarify its role in Latin Americans. Finally, we suggest that IL8RB-rs3890158G>A is a cis-regulatory SNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Despite the absence of epidemiological data, recent studies demonstrate that different forms of cancer are associated with a higher (or lower) contribution from Native American ancestry in admixed populations from South America. The investigations were associated with acute lymphoblastic leukaemia [ 44 ], breast cancer [ 45 ] and gastric cancer [ 45 – 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the absence of epidemiological data, recent studies demonstrate that different forms of cancer are associated with a higher (or lower) contribution from Native American ancestry in admixed populations from South America. The investigations were associated with acute lymphoblastic leukaemia [ 44 ], breast cancer [ 45 ] and gastric cancer [ 45 – 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 24 included publications (Table 2 [ 27 - 49 ]), 11 were reports on gastric cancer and 13 on colorectal cancer; 14 were studies in Asian populations, 8 in Caucasian populations, and 2 in mixed populations. The HWE examination results of the distribution of genotypes in the control group are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a large study which included 362 GC patients from Lima, Peru fond that IRF4 (OMIM #601900), ELMO1 (OMIM #606420), CLIP4 (OMIM #605736) and MSC (OMIM #603628) promoter methylation coupled with a GDMI > 4 are useful molecular tools for GC risk stratification in endoscopic biopsies (Pirini et al, ). An interesting study in native Peruvians (Quechuas from the Central Andes) did not found an association between candidate SNPs and GC (Zamudio et al, ).…”
Section: Healthcare Services Of Genetics and Genomicsmentioning
confidence: 99%